Casa GGG and Casa Negro - Alberto Kalach; Daniel Alvarez (Oz, 1999)
Casa GGG The house could be seen as the most simple and yet the most complex and exciting architectural theme. I understand it as a passage that transports inhabitants from every day life of the street to an inner world of intimacy.